Antioxidant enzymes activity and gene expression in wheat-stripe rust interaction at seedling stage. (March 2023) - Zainy, Zainy; Fayyaz, Muhammad; Yasmin, Tayyaba; Hyder, Muhammad Zeeshan; Haider, Waseem; Farrakh, Sumaira
Abstract: The current study was designed to determine the activity of antioxidant enzymes: superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione peroxidase GPX and catalase (CAT) and the expression of their genes in 10 wheat isogenic differential lines showing compatible and incompatible interactions with Puccinia striiformis . The enzyme activity was determined at 24 h after inoculation (24hai), 48 h after inoculation (48hai), and 72 h after inoculation (72hai). However, enzyme gene expression was determined only at 72hai. To fulfill the objectives, 12-day-old wheat seedlings of isogenic differential lines were inoculated with stripe rust race (race 574232). The results of the study showed that enzyme activity and gene expression was significantly high in incompatible interaction as compared to compatible interaction. The enzyme activity of SOD was high at 24hai in resistant isogenic differential lines. High enzyme activity (97.54 ± 4.84) was recorded in was recorded Yr5/6* Avocet S. Enzyme activities of CAT and APX were higher at 72hai in resistant isogenic differential lines. CAT, APX genes were significantly upregulated and while gene expression of SOD was low at 72hai. The results indicate a unique pattern of enzyme activity and gene expression of the antioxidant enzymes in the compatible and incompatible interaction is playing a crucial role in the plant defense system. Highlights: Antioxidant enzymes activity was remarkably increased incompatible interaction of wheat- Puccinia striiformis interaction. Antioxidant enzyme SOD activity and transcript level was high at 24hai. Antioxidant enzymes CAT and APX activity and transcript level was high at 72hai.